Biodiesel: Exploration of Microalgae as Feedstock, Methods, Production, and Characterization - Sri Rahmawati; Sri Wahyuni (International Journal of Sustainable English Language, Education, and Science, 2026)
Microalgae have emerged as a promising feedstock for biodiesel due to their high lipid content, rapid growth rate, and minimal land requirements compared to conventional oil crops. This review provides a comprehensive analysis of current research on microalgae-based biodiesel, covering feedstock selection, oil extraction methods, production processes, and product characterization. Literature from 2000 to 2025 was systematically analyzed, focusing on microalgae species with high lipid yield, ultrasonic and solvent extraction techniques, transesterification methods using acid and base catalysts, and physicochemical properties of the produced biodiesel. Key advantages of microalgae include sustainable cultivation, high productivity, CO₂ mitigation, and the potential for generating valuable co-products such as proteins and carbohydrates. Challenges such as optimization of lipid content, extraction efficiency, and large-scale production are also discussed. The review highlights trends, knowledge gaps, and future directions, emphasizing the potential of microalgae to support sustainable biodiesel production and contribute to renewable energy development